Synthesis of thermally stable porous SiC hollow spheres and control of the shell thickness - Noh, Seong-Cheol; Lee, Seung-Young; Kim, Sungrye; Yoon, Sungho; Shul, Yong Gon; Jung, Kwang-Deog (ELSEVIER, 2014)
Thermally stable SiC hollow spheres were prepared using SiO2 templates with two layers. At the calcination at higher than 1300 degrees C, the SiC hollow sphere could be obtained. The shell thickness of the porous SiC hollow spheres can be controlled by the molar ratio of TMS/TEOS. The pore volumes and BET surface areas of the template SiO2 increased with the molar ratio of TMS/TEOS, while those of the SiC/SiO2 and SiC spheres decreased. It is evident that the pore sizes of the SiC hollow spheres were not influenced by the TMS/TEOS ratio. The wall thickness of the SiC sample increased with an increase in the TMS/TEOS mole ratio. The prepared SiC hollow spheres with the surface area higher than 770 m(2)/g were thermally stable up to temperatures higher than 700 degrees C. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: SURFACE-AREA; SILICON; RECOMMENDATIONS; FABRICATION